Silver(I)‐Catalyzed Route to Pyrroles: Synthesis of Halogenated Pseudilins as Allosteric Inhibitors for Myosin ATPase and X‐ray Crystal Structures of the Protein–Inhibitor Complexes (Eur. J. Org. Chem. 21/2014). Issue 21 (July 2014) - Martin, René; Risacher, Célia; Barthel, André; Jäger, Anne; Schmidt, Arndt W.; Richter, Sabine; Böhl, Markus; Preller, Matthias; Chinthalapudi, Krishna; Manstein, Dietmar J.; Gutzeit, Herwig O.; Knölker, Hans‐Joachim
Abstract : The cover picture shows a ribbon presentation of the X‐ray crystal structure of the Dictyostelium discoideum myosin‐2 motor domain complex with magnesium(II)–adenosine diphosphate–metavanadate and pentabromopseudilin on the left side and a close‐up of the pentabromopseudilin binding site in this complex on the right side. Details are discussed in the article by H.‐J. Knölker et al. onp. 4487 ff. We are grateful to Dr. Roman Fedorov for the generation of this cover.